Oxidation during normal and vacuum packed storage of smoked carp - Alivuk, Edita (Jihočeská univerzita, 2018)
The purpose of this study was to investigate the effect of normal and vacuum package systems on the development of lipid-protein oxidation and firmness of common carp fillet through 3 weeks storage at +4°C. TBARS, carbonyls and firmness were measured in time 0 and 1 week for samples packed under normal package system and 0, 1, 2 and 3 weeks for samples stored under vacuumed packed system. Results showed significant difference between the fillets stored under different packing conditions. Lipid oxidation by respect to TBARS, indicate no significant difference in amount of TBARS in both package systems. However, protein oxidation showed significantly higher values of carbonyl content in normal packing compared to vacuum packing fillets. Firmness analysis results showed significant increase of the fillet firmness in nrmal packing after 1 week and decrease in the vacuum packing after 3 weeks storage. The results emphasized development of lipid and protein oxidation was more promoted in the carp fillets which were packed under normal storage.
Oxidation during normal and vacuum packed storage of smoked carp
Keywords: smoked carp fillets; firmness; protein oxidaton; lipid oxidation; vacuum package; normal package; storage +4°C; smoked carp fillets; firmness; protein oxidaton; lipid oxidation; vacuum package; normal package; storage +4°C